Eight dates : essential conversations for a lifetime of love - Gottman, John, ....-; Gottman, Julie Schwartz, ....- (New York : Workman Publishing, 2019)
From the leading research scientist on marriage and family and author of the million-copy bestseller The Seven Principles for Making Marriage Work, a program of eight lively, conversation-based dates for couples to capture essential conversations for a lifetime of love and commitment.